Faktor-Faktor Penggunaan Digitalisasi Banking Terhadap Perubahan Perilaku Transaksi Nasabah Bank Syariah Indonesia KCP Ciamis - Ganjar Santika; Ikmal Mumtahaen; Lu’luatun Najmi Fauzia Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to analyze whether there are factors for the use of digital banking and how they influence changes in customer transaction behavior at Bank Syariah Indonesia KCP Ciamis. The type of data in this study is quantitative. With primary data sources. This study uses a census sampling technique, which means that all 100 customers are respondents. This study used data collection techniques using a questionnaire with a Likert scale. And using multiple linear regression analysis. Based on the results of multiple regression analysis, the factors of using banking digitization obtained 0.169 (performance expectation factor), 0.277 (business expectation factor), 0.256 (Social Influence factor), 0.200 (Facilitating Condition factor), and collectively obtained 2.193. Based on the results of the t test, the factors for using digital banking include Performance Expectations (X1), Business Expectations (X2), Social Influence (X3), and Facilitating Conditions (X4) to obtain t values of 2.062 (X1), 2.522 (X2) , 2.718 (X3), 2.045 (X4) is greater than t table, namely 1.660, it can be concluded that the factors of performance expectations, business expectations, Social Influence and Facilitating Conditions have a significant positive effect on changes in customer transaction behavior at Bank Syariah Indonesia KCP Ciamis (Y). based on the results of the f test, the factors using banking digitization obtained an f count of 58.074 greater than the f table, namely 3.51. It can be concluded that the factors using banking digitization have a positive effect on changes in customer transaction behavior at BSI KCP Ciamis simultaneously.